The Perceptions of Overweight and Obese Individuals Regarding Weight-Loss Dietary Supplement Advertisements: A Pilot Cross-Sectional Survey - Zamzuri, Nik Nur Anis Ilyany; Hamdan, Nor Elyzatul Akma; Jamludin, Nurul Ashikin; Shaari, Mohammad Suhaidi; Taridi, Nur Syazwani; Abd Wahab, Mohd Shahezwan; Jamal, Janattul Ain (Journal of Public Health and Pharmacy, 2024)
Introduction: The negative health consequences of overweight and obesity underscore the importance of weight loss in mitigating these issues. Weight-loss dietary supplements (DS) are highly sought-after by overweight or obese individuals, with widespread advertisements promoting their use. This study aimed to investigate the perceptions of overweight and obese individuals regarding weight-loss DS advertisements. Methods: Over a six-week period from 5th April to 17th May 2023, an online pilot cross-sectional study was conducted targeting overweight and obese individuals in Malaysia. The study utilized a convenience sampling method to recruit participants. Results: Of the 146 participants, most were female (82.9%), 53.4% were overweight, and 46.6% were obese. Most respondents believed that weight-loss DS advertisements often contained exaggerated, unverified, and misleading information. Nearly 90% acknowledged that exaggerated advertisement claims might influence consumers, and about 85% believed that people are influenced to buy frequently advertised weight-loss DS. Despite these perceptions, about 40% reported purchasing a weight-loss DS after seeing such a product in an advertisement, while less than 50% of those who purchased weight-loss DS sought information from healthcare professionals. Conclusion: The study found that almost 40% of the respondents had purchased a weight-loss DS after seeing such products being advertised. Individuals with higher income, married people, and older respondents appeared more likely to purchase a weight-loss DS. These findings underscore the necessity for stricter regulatory frameworks and comprehensive consumer education initiatives to protect consumers from misleading information and unethical marketing tactics within the weight-loss DS industry. Implementing targeted public health interventions could further safeguard consumers from the risks associated with exaggerated product claims.